Endonasal Endoscopic Release of a Delayed Tension Pneumocephalus After Craniofacial Resection of a Tumor of the Anterior Skull Base - Krischek, Boris; Vescan, Allan; Zweifel, Christian; Zadeh, Gelareh; Gentili, Fred (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Tension pneumocephalus is a rare complication that can occur after craniofacial resection of lesions of the anterior skull base. Early diagnosis is important to avoid potential serious neurologic deficits, including death. It has been associated with the perioperative placement of a lumbar drainage and with esthesioneuroblastoma. Therapy consists of evacuation of the intracranial air as well as conservative measures. Here we report a case of a patient with an ethmoidal esthesioneuroblastoma who underwent a traditional microsurgical craniofacial resection and developed a delayed epidural tension pneumocephalus. This was treated by performing an incision in the pericranial flap covering the anterior cranial base defect using an endonasal endoscopic approach. To our knowledge, this particular treatment technique has not been reported before in this context.
Keywords: tension pneumocephalus; endonasal endoscopic approach; craniofacial resection; pericranial flap